Effect of the magnetic field on the interaction with two the types of fungus Fusarium sp.and The fungus resistance biogenic Trichoderma harzianum In the analysis of some chemical pesticides: Adeeb Kitab Abid Zaid Alshafiee 1Salwan A. Zahra Jabbar Allwbaw - Allwbaw, Salwan A. Zahra Jabbar; Alshafiee, Adeeb Kitab Abid Zaid (Journal of Kerbala for Agricultural Sciences, 2018)
Sought This study to analyze the residuse of pesticides the use of the magnetic field and interaction with two the types of fungus Fusarium sp.and The fungus resistance biogenic Trichoderma harzianum where s is the use of five types of pesticides chemical an RIDOMIL GOLD Fengicides , Esther ASTER Insecticide and NOMOLT and two CHEVALIER and Palace PAALAS Herbicides, by exposing to intensive magnetic field and at different times 24and 48 and 72 and 144 and 720h. the biological analysis was done interaction with two the types of fungus Fusarium sp.and The fungus resistance biogenic Trichoderma harzianum.shows that the chemical pesticides ASTER and NOMOLT analysis by the magnetic field after exposure for a period of 24,48and 144 h the pesticide ASTER affect the fungi Fusarium oxysporum and the pesticide NOMOLT affect the fungi Fusarium graminearum terms of (17.12,36.36)%respectively . The chemical pesticides CHEVALIER and PAALAS Do not degrade pesticides magnetic field only by a simple and affect the chemical pesticides CHEVALIER and PAALAS on the fungus resistance biogenic Trichoderma harzianum terms of (92.92,80.83)% respectively ,and for pesticidesRIDOMIL GOLD analysis after the magnetic field for a period of 24 hours and affect the fungi Fusarium graminearum terms of (65.38)%